(untitled) (Decentering European studies: perspectives on Europe from its beyond, 2025)
Integrated care reforms have been introduced across the globe in the face of demographic and epidemiological transitions, increasing threats of fragmented healthcare delivery, and mounting healthcare expenditure. Although these reforms have facilitated and shaped a shift in global healthcare policy and practice, the pace and pattern of reform adoption have differed across various countries. Among them, both China and Norway have been considered “reluctant reformers.” This chapter interrogates the policy rhetoric in this transition and examines areas of divergence in reform strategies between both country. Using the structural-instrumental and cultural-institutional perspectives, this study traces the reform process in both nations and analyzes how China and Norway have initiated and implemented their respective integrated care reforms, concluding that Norway’s path has been smoother that China’s due to existing formal structures and cultural acceptance, while China has faced complex governance challenges and the risk of symbolic implementation.